High-Performance Membranes Based on Spherical-Beaded Nanofibers and Nanoarchitectured Networks for Water-in-Oil Emulsion Separation - Li, He; Che, Keyi; Jiang, Pan; Yin, Fei; Li, Zhaoling; Wang, Xianfeng; Yu, Jianyong; Zhang, Shichao; Ding, Bin (Nano letters, 2024)
High-performance separation materials for oil–water emulsions are crucial to environmental protection and resource recovery; however, most existing fibrous separation materials are subject to large pore size and low porosity, resulting in limited separation performance. Herein, we create high-performance membranes consisting of spherical-beaded nanofibers and nanoarchitectured networks (nano-nets) using electrostatic spinning/netting technology, for water-in-oil emulsion separation. By manipulating the nonequilibrium stretching of jets, spherical-beaded nanofibers capable of generating a robust microelectric field are fabricated as scaffolds, on which charged droplets are induced to eject and phase separate to self-assemble nano-nets with small pores. Benefiting from 3D undulating networks with cavities originating from 2D nano-nets supported by 1D spherical-beaded nanofibers, the membranes exhibit under-oil superhydrophobicity (>152°), a striking separation performance with an efficiency of >99.2% and a flux of 5775 L m–2 h–1, together with wide pressure applicability, antifouling, and reusability. This work may open up new horizons in developing fibrous materials for separation and purification.